(untitled) (Acta Scientiarum. Health Sciences, 2025)
The use of drugs to promote bone regeneration and accelerate tissue repair is a growing field of research, especially in cases of significant bone loss. Isradipine, a calcium channel blocker traditionally used to treat hypertension, has shown potential effects on bone metabolism, suggesting a possible role in promoting bone repair processes. The present study investigated bone repair after tooth extraction in Wistar rats and assessed the effects of Isradipine administration. Forty-eight male rats, approximately 90 days old and weighing an average of 250 g, were randomly divided into two groups: Control and Experimental. In the Control group, only the extraction of the upper left central incisor was performed, whereas in the Experimental group, Isradipine (2.5 mg) was administered intraperitoneally after tooth extraction. The animals were euthanized at days 3, 7, 14, and 21 for histological analysis of bone repair. Histological analysis revealed that, at 3 days, both groups showed sockets filled with blood clots and initial inflammatory cells, without bone trabeculae. By day 7, the Control group exhibited immature osteoid tissue, whereas the Experimental group had a greater number of fibroblasts. At days 14 and 21, bone formation advanced in both groups, with denser bone tissue observed in the Experimental group. These findings underscore the potential of Isradipine to enhance bone repair and suggest promising avenues for the application of calcium channel blockers in bone tissue bioengineering.